1980
DOI: 10.1111/j.1423-0410.1980.tb01848.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Anti‐A from a Hybrid‐Myeloma: Evaluation as a Blood Grouping Reagent

Abstract: A monoclonal anti-A antibody has been evaluated and found suitable for use as a potent routine ABO grouping reagent, without the use of additives. The IgM anti-A (MH2/6D4) is secreted into the tissue culture supernatant by a permanent line of cloned cells derived by fusion of anti-A producing spleen cells and a mouse myeloma cell line. This is a cost-effective reagent which should reduce production costs by over 50%. This reagent has the advantages inherent in monoclonal antibodies among them the availability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
5

Year Published

1981
1981
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(58 citation statements)
references
References 10 publications
1
52
0
5
Order By: Relevance
“…Our study describes a novel human erythrocyte cell surface antigen different from any other erythrocyte or leukocyte antigen previously identified with either alloantisera or monoclonal antibodies (13,(22)(23)(24)(25)(26) number of erythrocyte antigens including Lutheran, Auberger, i, and P1 (9,10). While the polysaccharide structures of the PI and i antigens are fairly well understood (11,27) Lu6.…”
Section: Discussionmentioning
confidence: 99%
“…Our study describes a novel human erythrocyte cell surface antigen different from any other erythrocyte or leukocyte antigen previously identified with either alloantisera or monoclonal antibodies (13,(22)(23)(24)(25)(26) number of erythrocyte antigens including Lutheran, Auberger, i, and P1 (9,10). While the polysaccharide structures of the PI and i antigens are fairly well understood (11,27) Lu6.…”
Section: Discussionmentioning
confidence: 99%
“…It gives a rapid tightly agglutinated tile reaction suitable for detecting the weaker types of B (AiB and B cord cells) encountered in routine grouping work. It can also be used reliably for automated typ- Twice-cloned antibody-producing hybrid cell lines have been adapted to growth in large tissue culture vessels and, on repeated passage, continue to secrete antibody of uniform properties [22], Large volumes of active culture supernatant generated by con tinuous growth have the advantage of re quiring far fewer screening tests than is cur rently needed to produce the same volume of human reagent from a large number of individually screened serum donations, con siderably easing the testing workload. More over, the low cost of £5 for the materials to make 1 litre of potent culture supernatant could be further reduced by using an accept ably diluted (table III) preparation of ac tive supernatant.…”
Section: Antibody Preparationsmentioning
confidence: 99%
“…In a recent study [22] we showed that monoclonal anti-A antibody produced in tissue culture by a line of antibody-secreting cells, MH2/6D4 is highly effective as a blood-typing reagent. These cells, derived by Köhler and Milstein's technique [15,16] of fusing antibody-producing spleen cells with a mouse myeloma line [14], are a per manent source of pure, defined anti-A im munoglobulin that could free human serum donations for other needed blood products.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure was ideally suited to the study of cell surface and tumour antigens and to providing reagents for cell fractionation (29-3 1). Monoclonal antibodies produced in this way were suitable for radioimmunoassays and for neuropharmacology (32), as blood group reagents (33) and for large scale purification of natural products (34). We also extended the hybrid myeloma technology to a second species-the rat (35) and to the production of bi-specific immunoglobulins (hybrid-hybridomas) (36).…”
Section: Hybrid Myelomasmentioning
confidence: 99%